(3JSejI ef oYQa eef oCHge aj GdYeOI (B( (3YeOI GdCMcGe (B)s - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ , J (B852 (3g`s ((3YHO GdYRjR Hf agO GdgGTei Gdeci s)
(3ChdgG (B:s
(3GdMeO ddg hUdi Gddg Ydi eMeO hBdg hSde JSdjekG CdN s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs